1999
DOI: 10.1111/j.1469-7793.1999.701ad.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the glycine response by Ca2+‐permeable AMPA receptors in rat spinal neurones

Abstract: In acutely isolated rat sacral dorsal commisural nucleus (SDCN) neurones, application of kainate (KA) reversibly potentiated glycine‐evoked Cl− currents (IGly) in a concentration‐dependent manner. The cellular events underlying the interaction between non‐NMDA receptors and glycine receptors were studied by using nystatin‐perforated patch and cell‐attached single‐channel recording modes. The action of KA was not accompanied by a shift in the reversal potential for IGly. In dose‐response curves, KA potentiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
1
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 48 publications
4
32
1
1
Order By: Relevance
“…This result suggested that the increases of glycine in the interstitium by theanine might have influenced dopamine release via glycine receptors. Although glycine is known as a major inhibitory neurotransmitter, glycine combines with the glycine binding site of the NMDA receptor and enhances excitatory neurotransmission (Xu et al 1999;Kuhse et al 1995;Nong et al 2003). Glycine enhanced NMDA evoked dopamine release, and 7-chloro-kynurenate, an NMDA antagonist, acting on a glycine site, markedly reduced this response (Martinez et al 1992); however, 5,7-DCKA injection did not prevent the increase of dopamine concentration by theanine injection in this study.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…This result suggested that the increases of glycine in the interstitium by theanine might have influenced dopamine release via glycine receptors. Although glycine is known as a major inhibitory neurotransmitter, glycine combines with the glycine binding site of the NMDA receptor and enhances excitatory neurotransmission (Xu et al 1999;Kuhse et al 1995;Nong et al 2003). Glycine enhanced NMDA evoked dopamine release, and 7-chloro-kynurenate, an NMDA antagonist, acting on a glycine site, markedly reduced this response (Martinez et al 1992); however, 5,7-DCKA injection did not prevent the increase of dopamine concentration by theanine injection in this study.…”
Section: Discussioncontrasting
confidence: 48%
“…From these data, we expected that not only glycine but also other factors were involved in the effect of theanine on dopamine concentration in the perfusate. It was shown that glycine is co-localized with GABA in astrocytes and interneurons (Ross and Soltesz 2001;Bureau and Mulle 1998;Xu et al 1999;Levi and Patrizio 1992), and glycine and GABA are released simultaneously and work synergistically on different targets (Bohlhalter et al 1994). We expected that the GABAergic nervous system may also be influenced by theanine injection and is involved in dopamine concentration increase in the perfusate; however we did not examined the effect of theanine on intersutitial GABA concentration and GABA receptors in this study.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Bearing in mind that ethanol alters intracellular Ca 2ϩ (for review, see Little, 1991;Simasko et al, 1999;Mennerick and Zorumski, 2000), interactions between ethanol and glycine receptors may involve mechanisms linked to intracellular Ca 2ϩ . Three recent studies have reported that glutamateinduced Ca 2ϩ entry greatly potentiates I Gly in spinal neurons or oocytes expressing glycine receptors (Xu et al, 1999(Xu et al, , 2000Fucile et al, 2000). However, the effects of glutamate on VTA glycine receptors have not been examined.…”
mentioning
confidence: 99%
“…Tyrosine phosphorylation of the ␤ subunit of GlyR has been shown to potentiate GlyR by a twofold increase in apparent agonist affinity (Caraiscos et al, 2002), an effect remarkably similar to that induced by IGF-1 on SON neuron GlyR. Other kinases (PKC, calcium calmodulin-dependent protein kinase II) are known to also potentiate GlyR but not through a change in agonist sensitivity (Xu et al, 1996(Xu et al, , 1999. Increased agonist affinity also implies enhanced desensitization, which could potentially result in a decreased effect of GlyR activation.…”
Section: Potentiation Of Glyr By Igf-1mentioning
confidence: 99%